Efeito de mediação do senso de coerência entre cárie dentária e qualidade de vida relacionada a saúde bucal em adolescentes - Tondolo Junior, Jocelito (2020)
Oral health related-quality of life (OHRQoL) comprises a multidimensional and subjective representation of the feeling of well-being, not being restricted to the physical and psychological effects of diseases, but also involving family and environmental spheres. Sense of coherence (SOC) tries to explain why some people remain healthy, in the face of stressful situations, while others fall ill. The objective of this study was to verify the mediation effect between SOC, clinical conditions and OHRQoL, as well as the other relationships between socioeconomic, clinical and subjective conditions of the adolescents. This is a cross-sectional study nested in a cohort study with 6 years of follow-up, which started in 2012 with a sample of 1,134 adolescents. The data in this study refer to adolescents followed up in 2018 (retention rate of 67.7%), totaling 768. Clinical, socioeconomic, sociodemographic and subjective variables related to oral health were evaluated. Dental caries was evaluated by the number of decayed, lost and filled surfaces (DMF-T index), OHRQoL through the questionnaire Child Perception Questionnaire (CPQ11-14). The SOC was collected using the Sense of Coherence scale (SOC-13). Other variables were obtained by semi-structured questionnaires. Mediation effects between SDC and OHRQOL were tested using structural equation modeling (SEM). SDC did not mediate between clinical variables and OHRQoL. However, individuals with high SOC had a lower impact on OHRQoL (p<0.00), showing a direct effect and of greater magnitude, when compared to dental pain and DMF-T index, on adolescents' QoLRSB. Adolescents who had dental pain, lower mother education and household income that visit to the dentist last year showed larger DMF-T. Individuals with high SOC showed less impact on OHRQoL (p<0.00). Individuals with great DMFT presented high impact on OHRQoL (p<0,03). Thus, psychosocial characteristics are important contributors to OHRQoL in adolescents, showing a direct effect between SOC and OHRQoL.